Regulation and Intervention of Intracranial Pressure - Ni Wayan Lisa Suasti (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Intracranial pressure is the total amount of pressure exerted by the brain, blood and cerebrocinal fluid in the rigid cranial space. Compliance is an indicator of the brain's tolerance for increased ICP, when compliance is exceeded, there will be a dramatic increase in the pressure/volume curve so that ICP will increase rapidly. In the injured brain, cerebral blood flow (CBF) is regulated to supply sufficient oxygen and substrates to the brain. Certain physiological factors such as hypercarbia, acidosis and hypoxemia cause vasodilation which causes an increase in CBF, seizure activity and fever will increase the level of brain metabolism and CBF. Cerebral edema is the most common cause of non-traumatic brain injury such as central nervous system infections, metabolic and systemic encephalopathy. Vasogenic brain edema occurs due to injury to the blood-brain barrier and increased capillary permeability in the area around the injury, or to inflammation, especially in CNS infections. Medical management of elevated intracranial pressure includes sedation, cerebrospinal fluid drainage, and osmotherapy with either mannitol or hypertonic salts.